Ready for Take-off? - The Economic Effects of Regional Airport Expansion - Philipp Breidenbach (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyzes whether the expansion of regional airports in Germany caused positive spillover effects on the surrounding economies, exploiting the deregulation of the European aviation market as a quasi-experiment. Such potential spillovers are often used as an argument for the substantial annual subsidies to airports. Previous evaluations often suffer from the problem of reverse causality, since Investment decisions are based on the economic conditions of the region. By contrast, the aviation deregulation under the Single European Market-initiative provides an exogenous incentive for investing in the expansion of existing regional airports. A difference in- differences approach is used to estimate the causal effects of this expansion on regional growth. The results are sobering, though, as there is no evidence for any positive spillover effects.
Keywords: R51; R42; H54; 330